1990
DOI: 10.1128/jvi.64.11.5290-5294.1990
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human T-cell leukemia virus type I (HTLV-I) provirus in an infected cell line and in peripheral mononuclear cells of blood donors by the nested double polymerase chain reaction method: comparison with HTLV-I antibody tests

Abstract: Human T-cell leukemia virus type I (HTLV-I) provirus DNA from the cultured cell line HUT 102 and from peripheral mononuclear cells (PBMC) of anti-HTLV-I antibody-positive Japanese blood donors was detected by the nested double polymerase chain reaction (PCR) method. This procedure consists of a first amplification and a second amplification with the products of the first amplification and primers interior to the first primers. Using this method, we demonstrated that it is possible to detect single-template DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Indeed, Saito et al (1989Saito et al ( , 1990 reported several cases of HTLV-I-seronegative and PCR-positive children who were born to HTLV-I carrier mothers. On the other hand, Matsumoto et al (1990) reported a correlation between PCR positivity and IF seropositivity in HTLV-I-infected donors. In the present study, we used the IF method for the serological test and investigated the level of HTLV-I infection among the children.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Saito et al (1989Saito et al ( , 1990 reported several cases of HTLV-I-seronegative and PCR-positive children who were born to HTLV-I carrier mothers. On the other hand, Matsumoto et al (1990) reported a correlation between PCR positivity and IF seropositivity in HTLV-I-infected donors. In the present study, we used the IF method for the serological test and investigated the level of HTLV-I infection among the children.…”
Section: Discussionmentioning
confidence: 98%
“…The PCR method has been used in both qualitative and quantitative measurement of proviral DNA (Ehrlich et al, 1990). Matsumoto et al (1990) used a nested doublc PCR method to examine PBMC from HTLV-I-seropositive blooddonor samples and found that 48 of 57 carriers had a high level with more than 200 copies in 1.5 x lo5 PBMC.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method is the polymerase chain reaction (PCR) which increases target DNA sequences to a detectable level (Saiki et al, 1985). The detection of HTLV-I proviral DNA in peripheral blood mononuclear cells (PBMC) of carriers by this method has been reported (Matsumoto et al, 1990;Nakayama et al, 1990;Ehrlich et al, 1990).…”
mentioning
confidence: 99%
“…Screening-positive blood donations underwent an indirect immunofluorescence (IF)-based confirmatory test for the presence of anti-HTLV-1 antibodies, as described previously. 15 In the case that more than two testers were undecided about an IF result, based on weak positive and negative references, the sample was classified as IF indeterminate.…”
Section: Routine Screening and Confirmatory Tests For Anti-htlv-1 Amentioning
confidence: 99%